Implementation of the Project for Strengthening the Profile of Pancasila Students (P5) at SD Negeri Cigadung 03 - Cindi Pebrian; Diah Sunarsih; Dedi Romli Triputra (Journal of Education Technology Information Social Sciences and Health, 2024)
Currently, many students do not behave and do not have character that is in accordance with Pancasila values. The aim of this research is to describe the implementation of the project to strengthen the profile of Pancasila students (P5) and the impact of implementing P5 at SD Negeri Cigadung 03. This research uses qualitative research methods with a qualitative descriptive approach. Interviews, observation and documentation were used in this research to collect data. There are three stages in implementing P5, namely the planning stage, implementation stage and evaluation stage. The impact of P5 implementation includes six dimensions. These dimensions are the dimension of faith and devotion to God Almighty and having noble character, the dimension of mutual cooperation, the dimension of global diversity, the dimension of critical reasoning, the creative dimension and the independent dimension.